Access to justice in public procurement: improving judicial review through lean thinking, proactive law and legal design - Kaave, Piia; Storsjö, Isabell; Heikkinen, Pirkko (Sciendo, 2025)
The ultimate goal of the public procurement remedies system is to effectively enforce procurement rules and ensure that tenderers can appeal against contract awards and other decisions as efficiently and quickly as possible. In Finland, multiple measures have been taken to make the public procurement appeal system more effective, but studies show that reforms have made it more difficult and less attractive to appeal. The current system does not adequately provide access to justice to economic operators and the conventional approach to reforms has not done the job. To radically improve the public procurement remedies system, we discuss the integration of lean thinking, proactive law and legal design to improve access to justice in the public procurement appeal system. Lean thinking, traditionally used in manufacturing, focuses on efficient value creation and continuous improvement, helping streamline processes and improve the quality of justice. Proactive law aims to create legal frameworks that prevent problems before they arise, promote positive outcomes and create opportunities and value. Legal design combines legal thinking with design thinking to make legal systems, including processes, policies and documents, more user-friendly, understandable, transparent and accessible. We identified the following dimensions that integrate these three approaches: proactivity, continuous improvement, user-centricity, multi-professional collaboration, streamlining processes and design dimensions. As a result, we argue that the integration of lean thinking, proactive law and legal design offers promising avenues to improve the efficiency and efficacy of the existing public procurement appeal system. However, to move forward, additional data and empirical studies are needed to further evaluate the current situation, test the integration and assess their impact on existing challenges.